End of life or short break care - outcome of children referred to a children's hospice in the UK. (24th May 2012) - Koodiyedath, B; Miller, M
Abstract : Palliative care in children involves the full cross section of childhood illness. Survival after referral to a Children's Hospice can vary from hours to many years. It is felt that survival depends on age of the child as much as the primary diagnosis. The course of the illness may influence the likelihood of being cared for at home or in the hospice following referral. Diseases with a more predictable course (cancer, SMA type 1) are more likely to die at home or in hospice. A review was done on all referrals to a single children's hospice in the UK, to understand the contribution of a children's hospice to palliative care. The dataset was examined of those referred to the Hospice during the calendar year 2000, 2005 and 2010, to understand the pattern of change in outcomes of the referral if any in the last decade. Relationship between the diagnostic category (ACT and Hospice), the interval between referral and death and the place of death were looked at. Results: The data showed the same pattern in the interval between referral and death in all three years - approximately 50% of children died within the same year of referral and more than 90% of those died within 6 months of referral. Children with diagnosis falling into the ACT category 1 and 3 comprise 75% of this group dying within a year of referral. The proportion of children dying at home with more predictable course remained the same in the last decade. But there is a proportionate increase in more children coming for end of life care at the hospice. Conclusion: Referrals are made to Hospices both for end of life care and supportive care. These are distinct patterns of care that may be hard to provide in the same service. Early referral is essential to get the best possible palliative care service and to build a good relationship with families by the care team. Children's palliative care needs flexibility.